A system for the acquisition and digital analysis of lower limb flow waveforms - Smith, Leonard (Division of Biomedical Engineering, 2018)
A PC based waveform acquisition and analysis system has been developed for use in aorta-iliac arterial assessment. A Motorola DSP56001 based system containing dual Analog to Digital converters is used to sample phase quadrature demodulated signals from a commercially available continuous wave Doppler unit. The Power Spectral Density is calculated using an autoregressive model from which the mean velocity waveform is calculated. This waveform is used to calculate the damping factor, vessel compliance and runoff resistance of a simple electrical model of the lower limb arterial circulation using a non-linear regression technique of curve fitting in the time domain. A pilot study using the system shows a significant separation (p < 0.001 Mann Whitney U-test) between the damping factors of a normal control group (quartile range = 0. 15 - 0.25 ; median = 0. 19) and a patient group with angiographically determined aorta-iliac arterial disease (quartile range = 0.45 - 0.89 ; median= 0.49).